2016
DOI: 10.1002/ca.22743
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoreceptors of the ligaments and tendons around the knee

Abstract: Proprioceptive inputs from the joints and limbs arise from mechanoreceptors in the muscles, ligaments and tendons. The knee joint has a wide range of movements, and proper neuroanatomical organization is critical for knee stability. Four ligaments (the anterior (ACL) and posterior (PCL) cruciate ligaments and the medial (MCL) and lateral (LCL) collateral ligaments) and four tendons (the semitendinosus (STT), gracilis (GT), popliteal (PoT), and patellar (PaT) tendons) from eight fresh frozen cadavers were harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…22 Likewise, there is agreement that these receptors are located peripherally (in the subsynovial layer), alongside blood vessels, sitting within interfascicular gaps of the ligament. 16,20,22 Similar MRCs have been found in other structures of the knee including the posterior cruciate ligament (PCL), collateral ligaments, menisci, joint capsule, and skin. 20,[23][24][25] In these structures, the same distribution of MRCs (concentrated around bony attachments) is observed.…”
Section: Histological and Neurophysiological Findingsmentioning
confidence: 56%
See 3 more Smart Citations
“…22 Likewise, there is agreement that these receptors are located peripherally (in the subsynovial layer), alongside blood vessels, sitting within interfascicular gaps of the ligament. 16,20,22 Similar MRCs have been found in other structures of the knee including the posterior cruciate ligament (PCL), collateral ligaments, menisci, joint capsule, and skin. 20,[23][24][25] In these structures, the same distribution of MRCs (concentrated around bony attachments) is observed.…”
Section: Histological and Neurophysiological Findingsmentioning
confidence: 56%
“…16,20,22 Similar MRCs have been found in other structures of the knee including the posterior cruciate ligament (PCL), collateral ligaments, menisci, joint capsule, and skin. 20,[23][24][25] In these structures, the same distribution of MRCs (concentrated around bony attachments) is observed. 20 The fibers, originating from these MRCs, form a network (alongside those originating from the ACL) resulting in an afferent signal.…”
Section: Histological and Neurophysiological Findingsmentioning
confidence: 56%
See 2 more Smart Citations
“…However, there remains some controversy about the types and precise location of mechanoreceptors in human ligaments [41]. For example, Cabuk and Cabuk [42] examined a small sample of human cadaver ligaments and tendons to determine the presence and distribution of mechanoreceptors. The reported that free nerve endings followed by Ruffini endings and Golgi-like endings were the most prevalent type of mechanoreceptors.…”
Section: Afferent Feedbackmentioning
confidence: 99%